Is left ventricular function reduced after ultra-endurance exercise?. (4th February 2022) - Witso, M; Sletten, OJ; Hisdal, J; Melau, J; Smiseth, OA; Remme, EW; Skulstad, H
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Norwegian Health Association Introduction: Ultra-endurance exercise can be harmful according to previous studies, indicated by reduction in functional parameters and increase in cardiac biomarkers. Changes in load and heart rate with exercise influence left ventricle systolic function, making assessment of standard echocardiographic examination difficult. Purpose: We investigated the effect of ultra-endurance exercise on myocardial function acutely and at restitution. Methods: We investigated 10 participants aged 46 ±7 years, before (baseline), within 142 ± 78 minutes after finish (post run) and 5-10 days after (restitution) an ultra-endurance race (3.8 km swimming, 180 km bicycling and 42 km running with a total elevation of 5200 m). Echocardiography was performed at the three time points, including cardiac morphology and -function. Ejection fraction (EF) and stroke volume (SV) were measured by Simpson biplane. Cardiac output was calculated from SV and heart rate (HR). Cardiac power was calculated as the product of CO, mean arterial blood pressure and the conversion factor to Watt (W) 0.00222. Global longitudinal strain (GLS) was calculated using speckle-tracking echocardiography, and myocardial work was calculated by non-invasive pressure-strain analysis. Results: Acutely after exercise, myocardial function by GLS (p = 0.002), myocardial work (p < 0.001), mitral annular plane systolic excursion (MAPSE, p = 0.003) and EF (p = 0.004) were substantially reduced compared to baseline, whereas cardiac power and cardiac output (CO) were maintained (see table and figure). Heart rate was moderately increased (p < 0.001). End-diastolic volume (EDV) as an index of preload was numerically, but not significantly reduced. End systolic volume (ESV) was numerically increased (p = NS) even though systolic blood pressure (sBP) was reduced (p = 0.01) post race. After restitution all parameters returned to baseline levels. Conclusions: The temporary reduced strain and EF may be a physiologic response due to the higher heart rate. However, despite reduced systolic pressure the heart did not contract to a lower end systolic volume. This suggests loss of contractile function compensated by increase in heart rate. The findings should be explored in further studies.